2017
DOI: 10.1146/annurev-pathol-052016-100247
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis: Mechanisms and Relevance to Disease

Abstract: Necroptosis is a form of regulated cell death that critically depends on receptor-interacting serine-threonine kinase 3 (RIPK3) and mixed lineage kinase domain-like (MLKL) and generally manifests with morphological features of necrosis. The molecular mechanisms that underlie distinct instances of necroptosis have just begun to emerge. Nonetheless, it has already been shown that necroptosis contributes to cellular demise in various pathophysiological conditions, including viral infection, acute kidney injury, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
424
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 532 publications
(427 citation statements)
references
References 199 publications
(298 reference statements)
2
424
0
1
Order By: Relevance
“…4B) significantly induced the phosphorylation of MKLK at Ser358 in PANC1 and PANC2.03 cells, suggesting that AURKA inhibits p-MLKL to suppress necroptosis. MLKL phosphorylation is controlled by its physical interaction with other core components of the necrosome, including RIPK1 and RIPK3 3, 4 Immunoprecipitation analysis showed that CCT137690 (Fig. 4C) or MLN8237 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B) significantly induced the phosphorylation of MKLK at Ser358 in PANC1 and PANC2.03 cells, suggesting that AURKA inhibits p-MLKL to suppress necroptosis. MLKL phosphorylation is controlled by its physical interaction with other core components of the necrosome, including RIPK1 and RIPK3 3, 4 Immunoprecipitation analysis showed that CCT137690 (Fig. 4C) or MLN8237 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Necroptosis is a caspase-independent form of regulated cell death that is induced by specific stimuli in apoptosis-resistant cells 3, 4 . The process of necroptosis involves activation of a series of specific proteins, namely receptor interacting serine/threonine kinase (RIPK)-1, RIPK3, and mixed lineage kinase domain-like (MLKL).…”
Section: Introductionmentioning
confidence: 99%
“…97 Such a chemokine mixture is particularly efficient at recruiting neutrophils towards the dying cells (a process that appears to be evolutionarily conserved), paving the way to the CALR-dependent phagocytosis of dying cancer cells or corpses thereof, and the cytotoxic targeting of residual malignant cells. 97 We characterized a naturally-occurring preclinical model of cancer that exhibits intrinsic resistance against mitoxantrone-induced ICD in vivo secondary to a defect in CALR exposure, 199 and we documented that anthracyclines and oxaliplatin can trigger a necroptotic variant of ICD [211][212][213][214][215] in cancer cells expressing receptor interacting serine/threonine kinase 3 (RIP3K) and the pseudokinase mixed lineage kinase domain-like (MLKL). 215 Finally, we found that an engineered oncolytic vaccinia virus 216 can induce ICDdependent antitumor immunity, which can be further potentiated by the co-administration of ICD-inducing chemotherapy or immune checkpoint blockers (ICBs), 216 and that pharmacological inhibition of signal transducer and activator of transcription 3 (STAT3) 217 signaling boosts the therapeutic efficacy of anthracyclines upon increased type I interferon (IFN) secretion.…”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%
“…2). The evolving evidence for each of these molecules and their molecular interactions has recently been elegantly described in detail [2]. Functional studies require specific modulation of these targets that can be achieved by either genetic targeting through the creation of mutant mice or by the help of pharmaceuticals with some, but often not entirely certain, target specificity.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
“…RIKP1 kinase activity is essential for RIKP3 phosphorylation in necroptosis. RIPK1 and RIPK3 auto- and transphosphorylate each other, which promotes the formation of the microfilament-like necrosome complex [2]. As such, RIPK3 is essential for necroptosis but is still also involved in other inflammatory pathways.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%